2019
DOI: 10.1093/ntr/ntz045
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Profile of Spectrum Reduced Nicotine Cigarettes

Abstract: Introduction Spectrum research cigarettes have been developed with varying nicotine content for use in studies evaluating the effects of a regulatory policy reducing the permissible nicotine content in cigarettes. This study aimed to characterize the nicotine pharmacokinetic profile of Spectrum cigarettes. Methods Twelve daily smokers attended four sessions and had blood nicotine, exhaled carbon monoxide, and subjective effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 33 publications
2
6
0
Order By: Relevance
“…It is unlikely that the lack of long-term effects of early and mid-adolescent tobacco smoke and nicotine exposure in the males was due to low nicotine levels. Plasma nicotine levels in the adolescent rats were similar to those in smokers, and previous work has shown that these nicotine levels are rewarding in adolescent male and female rats (Kamens et al, 2019;Xue et al, 2018).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…It is unlikely that the lack of long-term effects of early and mid-adolescent tobacco smoke and nicotine exposure in the males was due to low nicotine levels. Plasma nicotine levels in the adolescent rats were similar to those in smokers, and previous work has shown that these nicotine levels are rewarding in adolescent male and female rats (Kamens et al, 2019;Xue et al, 2018).…”
Section: Discussionsupporting
confidence: 67%
“…Exposure to tobacco smoke from low-nicotine cigarettes led to a plasma nicotine level of about 6 ng/ml, and exposure to smoke from high-nicotine cigarettes led to a plasma nicotine level of about 40 ng/ml. The plasma nicotine levels after exposure to smoke from the high-nicotine cigarettes (NRC 600) were similar to those in humans after smoking these high-nicotine cigarettes (Kamens et al, 2019). Similar nicotine levels were also observed in a heavy smoker after smoking their regular cigarettes (Russell et al, 1976).…”
Section: Discussionsupporting
confidence: 59%
“…18,19 A recent study examining the pharmacokinetic profile of Spectrum cigarettes found that, as expected, boosts in plasma nicotine concentration were reflective of the nicotine content of the cigarettes, also suggesting that compensatory smoking is not occurring with these reduced nicotine content cigarettes. 44…”
Section: Discussionmentioning
confidence: 99%
“…This is due to reduced nicotine intake and cigarette consumption over the duration of use. KAMENS et al (29) compared the pharmacokinetic profile of SPECTRUM®/VLN™ cigarettes to usual brand after a single use in twelve daily cigarette smokers. Nicotine area under the curve was reduced by 95%.…”
Section: Discussionmentioning
confidence: 99%